2012
DOI: 10.1111/j.1600-6143.2011.03762.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Antagonists Prevent Costimulatory Blockade-Resistant Transplant Rejection by CD8+ Memory T Cells

Abstract: The success of belatacept in late-stage clinical trials inaugurates the arrival of a new class of immunosuppressants based on costimulatory blockade, an immunosuppression strategy that disrupts essential signals required for alloreactive T cell activation. Despite having improved renal function, kidney transplant recipients treated with belatacept experienced increased rates of acute rejection. This finding has renewed focus on costimulatory blockade-resistant rejection and specifically the role of alloreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 66 publications
2
80
0
Order By: Relevance
“…However, the majority of those studies focused on tolerance induction that used a short treatment course of costimulation blockade, whereas in this study we treated continuously with CTLA4-Ig, which is similar to its clinical use (1,2,34). Furthermore, most of those studies were based on the adoptive transfer of donor-reactive memory T cells that drove the costimulation blockade-resistant rejection process (11,28,35,36). While that approach, especially when using graft-reactive TCR-transgenic T cell transfer, allows for elegant in-depth mechanistic analysis, their presence at nonphysiologically high TCR affinities and frequencies can lead to observations not replicated with endogenous T cells (37,38), and can also profoundly enhance endogenous graft-specific responses (39).…”
Section: Cd4mentioning
confidence: 99%
“…However, the majority of those studies focused on tolerance induction that used a short treatment course of costimulation blockade, whereas in this study we treated continuously with CTLA4-Ig, which is similar to its clinical use (1,2,34). Furthermore, most of those studies were based on the adoptive transfer of donor-reactive memory T cells that drove the costimulation blockade-resistant rejection process (11,28,35,36). While that approach, especially when using graft-reactive TCR-transgenic T cell transfer, allows for elegant in-depth mechanistic analysis, their presence at nonphysiologically high TCR affinities and frequencies can lead to observations not replicated with endogenous T cells (37,38), and can also profoundly enhance endogenous graft-specific responses (39).…”
Section: Cd4mentioning
confidence: 99%
“…According to this paradigm, chemokines displayed on the inflamed endothelium engage Gα i -coupled chemokine receptors on rolling T cells and trigger their firm adhesion and transmigration via integrin-dependent mechanisms (7). Although blocking integrins has been shown to reduce T cell infiltration and delay graft rejection (8,9), targeting individual or multiple chemokine receptors has had modest or no effects (10)(11)(12). This prompted us to reexamine the role of Gα i -coupled chemokine receptors in the migration of effector and memory T cells to vascularized organ transplants.…”
Section: Introductionmentioning
confidence: 99%
“…On day 30 after infection, animals were challenged with an OVA-expressing skin graft and treated with immunosuppressive regimens consisting of an integrin blocker (anti-VLA-4) combined with either CTLA-4 Ig or anti-CD28 dAb ( Figure 1C). Anti-VLA-4 has been previously shown to be synergistic in inhibiting memory CD8 + T cell-mediated graft rejection when combined with CTLA-4 Ig and anti-CD154 (43). Animals receiving the CTLA-4 Ig-based immunosuppression rejected their grafts with an MST of 22 days ( Figure 1D), while those animals that received the anti-CD28 dAb-based immunosuppression experienced significantly prolonged allograft survival (MST undefined, >100 days; Figure 1E).…”
Section: Cd8mentioning
confidence: 99%
“…First, these data demonstrate differences in the quantity and quality of donor-reactive memory CD8 + T cells elicited via distinct types of exposure and highlight the fact, as we previously reported (31), that the heterogeneity of alloreactive CD8 + T cell memory might necessitate tailored therapeutic targeting for optimal control. We previously showed that antagonism of either LFA-1 or VLA-4 synergized with a regimen consisting of CTLA-4 Ig and anti-CD154 to prolong survival in animals possessing donor-specific CD8 + memory T cells elicited via the Listeria-OVA system used here (54). We now report that anti-CD28 dAb is effective at prolonging graft survival in this model in the absence of CD154 antagonism, a finding that is highly clinically relevant in that progress of CD154 blockers in the translational pipeline has been slow and the path to FDA approval for these reagents is currently uncertain (55).…”
Section: Discussionmentioning
confidence: 99%